THE USE OF DIGITAL AUDIO IN ENHANCING EFL LEARNERS’ LISTENING PROFICIENCY - Intan Angelia Sihombing; Debora Chaterin Simanjuntak (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Listening is a critical ability to have, not only because of the time it takes in interactions but also because of its role in daily life. This study has been designed to explore the use of digital audio in promoting listening proficiency. Further research is required to determine how this position affects speakers of Indonesian who are learning English as a foreign language (EFL). A comparative study served as the foundation for this study's design. In this study, the research participants were at the upper secondary level, and their listening ability was examined in relation to the effects of digital audio (online podcasting on Spotify). Sixty students were involved in the study based on their performance on the placement test. Findings from the post-test showed that the group exposed to digital audio experienced an increase in their listening proficiency level, while the group not exposed to digital audio showed a little improvement in their proficiency level. By looking at the N-gain of their results, the group whose participants were not taught using active listening had an N-gain of 0.62, while the improvement of the second group resulted in an N-gain of 0.76, indicating that the group increased their listening proficiency level. The findings of this study showed that, with a result of 0.0235, there was no significant difference between the two teaching groups, where the significant value was greater than 0.005. claiming that while there is some difference between the two methods, it is not very much, and that both improve listening skills.